Highlights in peptide nanoparticle carriers intended to oral diseases - Benergossi, Jessica [UNESP]; Calixto, Giovana [UNESP]; Fonseca-Santos, Bruno [UNESP]; Aida, Kelly Limi [UNESP]; Negrini, Thais de Cassia; Duque, Cristiane [UNESP]; Daflon Gremiao, Maria Palmira [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publ Ltd, 2015)
New biocompatible nanomaterials are leading to a range of emerging health treatments. Thus, peptide drugs present in oral diseases, such as caries, periodontal diseases and oral cancer, are highlighting into clinical practice because the peptides can have an influence the growth of tumor cells or microorganisms and its can exhibit direct cytotoxic activity towards cancer cells or microbial cells. Therefore, it is interesting to speculate what are the natural or synthetic peptides that can be used to develop novel strategies to fight cancer diseases or microbial cells, and so, to represent a novel family of anticancer or antimicrobial agents. The use of buccal drug delivery systems, especially nanoparticles, to carrier peptides shows to be very interesting, because these systems can protect the peptide against enzymatic degradation, in addition to target inaccessible sites. However, this peptide delivery system seems to be unexplored by researchers. On the hand, the application of drug delivery systems for oral diseases could be a proposed treatment for these diseases, including the treatment or co-treatment with other therapies, such as photodynamic therapy, of antimicrobial, periodontal diseases and cancer, or even in the early diagnosis of cancer. The objective of this study is to present a systematic review of nanotechnology-based peptides delivery systems intended to oral diseases.
Keywords: Peptide drugs; Targeted delivery; Dental caries; Periodontal diseases; Oral squamous cell carcinoma